Analisis Makna Asosiasi dalam Puisi Hujan Lolos di Sela Jari Karya Yudhiswara: Kajian Semantik - Katharina Woli Namang; Aulia Fitri Syaharani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Association is the process of changing meaning as a result of similar characteristics. The meaning contained in a word will sometimes experience a change in meaning/shift in meaning when the word is combined with other words. This research aims to find out the words that have association meaning in Yudhiswara's poetry collection Rain Escapes in Sela Jari. The research method in this study is descriptive qualitative. The theory used in this research is the theory of semantic studies on changes in meaning. The data in this research is in the form of words, phrases/idioms that have associations and the data source in this research is a collection of poems Hujan Lolos di Sela Jari by Yudhiswara. The data collection technique in this research uses reading and note-taking technique. The data analysis technique in this research is classifying the data including metaphorical meaning changes, analyzing the data and making conclusions. The results of this study indicate that the poem Rain Escapes in Sela Jari is in the form of compound words that contain associations of meaning, the association of meaning tells about love and tells about nature. This shows that in the poem that has been analyzed, the poet uses many words, phrases/idioms to express the feelings experienced by the reader. The reader is also carried away when reading a poem that tells about love that is hindered by time, circumstances, and places.